The Strategy in Developing Global Competitive Tourism Based on Creative Economy and Local Wisdom (Case Study: Solo City, Indonesia) - Haryo Kusumo Aji; Andika Drajat Murdani; Hasna Wijayati (International Journal of Business and Applied Economics, 2023)
Solo City has developed into a City of Culture that carries the power of local wisdom. One of the development directions of the city of Solo is towards the tourism sector and creative economy based on local wisdom. This research aims to find out the strategy of Solo City in developing globally competitive tourism and creative economy based on local wisdom. The research was conducted using qualitative methods. Data was collected through interviews and observation methods. The analysis of the research results shows that the City of Solo is able to develop tourism competitiveness globally through strong synergy between the driving actors. The Solo City Government plays an important role in facilitating creative economy activities and branding and local wisdom. This is supported by the common perception of the people of Solo City who also support the direction of Solo City policy.